College EFL teachers’ beliefs in making requests - Chen, Chiung-chiuen (Advances in Social Sciences Research Journal, 2020)
This study examined college EFL teachers’ beliefs in their making requests in the classrooms. In this study, the methods for data-collection included a questionnaire, classroom observation, and an in-depth interview. A pre-observation questionnaire was administrated for collecting the information on teacher belief in the use of request types, and why and when teachers made these requests. Five EFL teachers and one of their respective English classes at university in Taiwan were invited to participate in the present study. Over a 4-week period, a total of 40 sessions of teaching, 50 minutes each, were observed, video-taped, and audio-taped. Afterwards, an interview was conducted. The data collected were transcribed, coded, and analyzed. Findings showed that all teachers reported their uses of both direct and indirect requests. Also, all teachers made their requests for some specific reasons and at some specific point of time. It is suggested that teachers be aware of their uses of requests. Teachers’ awareness of their uses of different types of requests may help promote teacher-student interaction.